Pengaruh Modeling Instruction Terhadap Kemampuan Pemecahan Masalah Fisika Pada Materi Usaha Dan Energi Siswa Kelas X MIPA SMA Muhammadiyah Mayong Jepara - Feny Indriyani; Joko Siswanto; Nur Khoiri (Universitas PGRI Semarang, 2018)
The purpose of this research is analyzing the impact of Modeling Instruction towards students’ ability in solving phisics problems on Work and Energy of X MIPA SMA Muhammadiyah Mayong Jepara. This research used pre-experimental design that held on January 29th 2018 untill January 5th 2018 academic year 2018/2019. The population of this research was the entire of X MIPA of SMA Muhammadiyah Mayong Jepara, and the sample selected randomly. So, as the result, X MIPA 1 becomes experiment class. The researcher used data documentation techniques, test and interview as data collecting techniques. Based on research result, there is impact of Modelling Instrucion towards students’ ability in solving phisics problems on Work and Energy material of X MIPA SMA Muhammadiyah Mayong Jepara through t test calculation, gained tcount = 43,026 > ttable = 2,028. While from the gain test analysis <g> gained 0,46 for experimental class in the medium category. Based on the data result, can be concluded that there is impact of Modelling Instrucion towards students’ ability in solving phisics problems on Work and Energy material of X MIPA SMA Muhammadiyah Mayong Jepara.